G106 Paediatric functional illnesses – learning points from the first year of a two year pilot service. (May 2019) - Sudarsan, N; Salter, H; Kendall, R; Adams, E; Krikman, J; Etkin, B; Beresford, S; Anderson, D
Abstract : Introduction: Medically unexplained or functional illnesses in children are associated with significant morbidity and healthcare costs due to delay in diagnosis and lack of bespoke services. Brighton and Hove CCG commissioned a 2 year pilot service for functional disorders in children based at the Royal Alexandra Children's Hospital, Brighton. Our one year experience highlights the challenges in service development and some key learning points. Observations: Although initially commissioned as a chronic pain service, during the yearlong consultation process it was agreed that a wider service covering all forms of functional illnesses was necessary. The team consists of paediatrician, physiotherapist, psychologist, occupational therapist and administrator. Key challenges during service development included scarcity of published evidence around physical and psychological therapies in children and outcome measures for service evaluation. Deciding on thresholds for escalation of safeguarding and self harm concern was also challenging. These were overcome through evidence search and consultation with existing services. Weekly work involves triaging team meeting, clinics and therapy sessions. Therapy involves one to one and group physiotherapy and psychology as well as Yoga and mindfulness. The service is also launching a group session for psychoeducation on mind –body interaction. School liaison and home visits are also part of rehabilitative work. A total of 35 patients were seen. Medically unexplained chronic pain (25) was the commonest reason for referral. Non epileptic attacks (3), and other (7) functional illnesses were also seen. Other functional illnesses included medically unexplained visual loss, swallowing difficulties and functional paralysis. 42% of children had school attendance of 75% or lesser and 20% were unable to attend school because of their symptoms. In chronic pain patients there was a high incidence of diagnosed or undiagnosed learning difficulties (55%) like dyslexia (36%), sensory processing issues (27%) and social communication difficulties (18%). PedsQL™, RCADS, school attendance, patient/referrer feedback, primary and secondary care services utilisation will be the key outcome measures. Conclusions: Our learning points in overcoming challenges in service set up will hopefully help aspiring services. Undiagnosed learning difficulties may well be a factor in the origin and perpetuation of functional illnesses along with other bio-psychosocial factors.